2015
DOI: 10.1589/jpts.27.531
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of muscle damage using ultrasound imaging

Abstract: [Purpose] This study aimed to quantitatively analyze characteristics of and changes in internal muscle structure according to the time of delayed onset muscle soreness (DOMS) using ultrasound imaging, thereby presenting clinical evidential data for evaluation of muscle damage. [Subjects] We recruited 38 male subjects. [Methods] Ultrasound images of the medial gastrocnemius muscle prior to induction of DOMS and immediately after, 24 hours after, 48 hours after, and 72 hours after induction of DOMS were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 25 publications
0
30
0
3
Order By: Relevance
“…In low-grade muscle damage such as DOMS, conventional ultrasound imaging of the concerned muscle tissue often appears normal or shows small hyperechoic areas regarding its echogenicity [54,63,64]. Focusing on indirect signs, damaged muscles exhibit mechanical property changes, which are closely related to changes in their internal structure, including fascicle length, pennation angle, and muscle thickness [48]. The pennation angle and muscle thickness has been shown to be increased after DOMS induction [48].…”
Section: Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…In low-grade muscle damage such as DOMS, conventional ultrasound imaging of the concerned muscle tissue often appears normal or shows small hyperechoic areas regarding its echogenicity [54,63,64]. Focusing on indirect signs, damaged muscles exhibit mechanical property changes, which are closely related to changes in their internal structure, including fascicle length, pennation angle, and muscle thickness [48]. The pennation angle and muscle thickness has been shown to be increased after DOMS induction [48].…”
Section: Ultrasoundmentioning
confidence: 99%
“…Focusing on indirect signs, damaged muscles exhibit mechanical property changes, which are closely related to changes in their internal structure, including fascicle length, pennation angle, and muscle thickness [48]. The pennation angle and muscle thickness has been shown to be increased after DOMS induction [48]. A comparison to the contralateral leg or follow-up examinations may reveal relevant information concerning these indirect signs (▶ Fig.…”
Section: Ultrasoundmentioning
confidence: 99%
“…A study by Dierking et al 8 in 2000 showed an increase in the cross‐sectional area of the biceps brachii with DOMS as measured with ultrasound, but this measurement lacked sensitivity in the diagnosis when compared to creatine kinase, muscle shortening, and subjective muscle soreness. In contrast, a study by Yu et al 7 in 2015 showed statistically significant increases in muscle thickness and the pennation angle of the medial gastrocnemius as measured with ultrasound as DOMS progressed over time. One additional report showed increased echogenicity of the brachialis in a patient with DOMS 6 .…”
Section: Discussionmentioning
confidence: 80%
“…One study by Tagliafico et al 6 in 2013 showed a single example of increased echogenicity of the brachialis muscle with DOMS. In addition, a recent study by Yu et al 7 in 2015 described an increased pennation angle of the muscle and the muscle thickness in DOMS. To our knowledge, no articles have been published fully characterizing the ultrasound features of DOMS.…”
mentioning
confidence: 95%
“…DOMS might be associated with ultrastructural muscle lesions that occur after unaccustomed exercise, especially after eccentric exercise [2]. This indirect muscle damage is associated with intramuscular oedema and raised CK levels, furthermore it causes pain, increased muscle tone [45] and decreased range of motion of adjacent joints [23]. DOMS is one of the most common reasons for impaired muscle performance in sports and is associated with reduced muscle strength and frequently observed in both professional and recreational athletes [23,33].…”
Section: Discussionmentioning
confidence: 99%